Biocompatible magnetic hydroxyapatite Fe3O4-HAp nanocomposites for T1-magnetic resonance imaging guided photothermal therapy of breast cancer. (June 2022) - Mushtaq, Asim; Tang, Zhe; Hou, Yike; Zhu, Zheng; Tian, Cong; Wu, Yuling; Lu, Yuguang; Iqbal, M. Zubair; Kong, Xiangdong
Abstract: Theranostic nanomedicine designs integrating diagnostic and therapeutic paradigms have been achieving considerable success at clinics. However, the toxicity of nanocomposites in these designs remains a major obstacle to the success of personalized medicine. Herein, highly biocompatible iron and hydroxyapatite materials were selected to design a Fe3 O4 -HAp nano-theranostic system with controlled dimensions using simple solvothermal synthesis. The biocompatibility of Fe3 O4 -HAp magnetic hydroxyapatite nanocomposites (MHNCs) was further enhanced by Food and Drug Administration- (FDA-) approved triblock copolymers, namely, Pluronic® F-127. Indeed, polymer modification improved the drug encapsulation capacity of HAp, and 70% anti-TROP 2 was loaded onto the surface of MHNCs for intracellular targeting of breast cancer. The Fe3 O4 component of MHNCs possessed a high T1 -MR imaging enhancement feature with an excellent r1 value, demonstrating these MHNCs as capable substitutes for Gd-based toxic contrast agents. Moreover, indocyanine green (ICG-) coupled-MHNCs revealed strong absorption in the near-infrared region and produced enough temperature (75 °C), even at low (50 ug/mL) concentrations, to ablate cancerous cells upon 808 laser irradiation to induce cell toxicity and apoptosis. The promising diagnostic and photothermal therapeutic performance of these designed MHNCs make them an ideal nano-theranostic agent. Graphical Abstract: ga1